Development of microalgae-bacteria granular sludge for the treatment of aquaculture wastewater - Amorim, Catarina L. (2019)
The use of microalgae–bacteria systems is particularly attractive for wastewater treatment as combining microorganisms with different metabolic machineries could allow the development of a robust biological system. The aim of this study was to evaluate the feasibility to develop microalgae-bacterial granular sludge through the self-immobilization of microorganisms under SBR mode. After the addition of the suspended microalgae consortia containing several strains isolated from an aquaculture facility, adhesion of microalgae to the bacterial granules was observed. Reactor removal performance for carbon and nutrients was followed to assess the effect of the microalgae bioaugmentation process.